Penning-trap Q-value determination of the 71Ga(ν, e−)71Ge reaction using threshold charge breeding of on-line produced isotopes - Frekers, Dieter; Simon, Martin C.; Andreoiu, C.; Bale, J. C.; Brodeur, Maxime; Brunner, Thomas; Chaudhuri, A.; Chowdhury, U.; Crespo López-Urrutia, José Ramon; Delheij, P.; Ejiri, H.; Ettenauer, S.; et al. (Physics letters, 2013)
We present a first direct Q-value measurement of the Ga71(ν,e−)Ge71 reaction using the TITAN mass-measurement facility at ISAC/TRIUMF. The measurements were performed in a Penning trap on neon-like 71Ga21+ and 71Ge22+ using isobar separation of the on-line produced mother and daughter nuclei through threshold charge breeding in an electron-beam ion trap. In addition, isoionic samples of 71Ga21+ and 71Ge21+ were stored concurrently in the Penning trap and provided a separate Q-value measurement. Both independent measurements result in a combined Q-value of 233.5±1.2 keV, which is in agreement with the previously accepted Q-value for the ν cross-section calculations. Together with a recent measurement of the ν-response from the excited states in 71Ge, we conclude that there are no further uncertainties in the nuclear structure, which could remove the persistent discrepancy between the SAGE and GALLEX calibration measurements performed with neutrinos from reactor-produced 51Cr and 37Ar sources and the theoretical expectation.
Im Titel ist "71" und "-" jeweils hochgestellt
Gesehen am 07.05.2021